Active Learning with Problem-Based Learning for Problem-Solving Skills in Social and Natural Sciences: Pembelajaran Aktif dengan Problem-Based Learning untuk Keterampilan Pemecahan Masalah pada Ilmu Pengetahuan Alam dan Sosial - Suci Aulia; Sundahry; Zulqoid R. Habibie (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The ability to solve problems is an essential 21st-century skill but remains limited in elementary science learning. Specific Background: At SDN 127/II Sungai Arang, students demonstrated difficulty in understanding science concepts, low participation, and low mastery of learning outcomes. Knowledge Gap: Conventional teaching methods were teacher-centered and failed to provide opportunities for students to actively explore solutions to real-world problems. Aim: This research aimed to describe how Problem-Based Learning (PBL) can improve the learning process, students’ problem-solving skills, and their science learning achievements. Results: This classroom action research was conducted in two cycles involving 19 students. Teacher activity scores improved from 64%–72% in Cycle I to 80%–92% in Cycle II. Student engagement rose from 57.89% to 89.48%, and learning mastery increased from 63.16% to 84.21%. Novelty: The study demonstrates the practical application of PBL in a resource-limited school setting, highlighting its potential to transform passive learning into an interactive experience. Implications: Findings suggest that PBL can serve as a model for curriculum development and teacher training to foster active learning and problem-solving culture in elementary education. Highlights: Students’ participation and confidence in solving problems increased in Cycle II. Teacher performance improved, shifting towards more student-centered facilitation. Learning mastery rose significantly after PBL implementation. Keywords: Active Learning, Problem-Based Learning, Problem-Solving Skills, Social and Natural Sciences, Elementary Education